The Effect of Celery Extract (Apium graveolens L.) Towards The Histological Structure of Rat’s Kidney (Rattus norvegicus) Induced by Ethylene Glycol - Husna, Nana Zaimatul; Mahriani, Mahriani; Wiyono, Hidayat Teguh (Metamorfosa: Journal of Biological Sciences, 2021)
The kidneys are an important excretory organ for removing the rest of the body's metabolism. Kidney stones can affect kidney function. Celery contains flavonoid compounds that can improve the histological structure of the kidneys. This study aims to determine the effect of celery extract on the histological structure of the kidneys, namely the diameter of the glomerulus and tubule with protein deposits. This research is experimental with completely randomized design (CRD). The treatment group was divided into 4 groups, namely, negative control (K-), rats were only given food and drink; positive control (K+), rats induced Ethylene glycol (EG) 0.75% +  Ammonium Chloride (AK)  2%, dose 1 (D1), rats induced EG 0.75% + AK 2% and celery extract 100 mg / kg, dose 2 (D2), rats induced EG 0.75% + AK 2% and celery extract 200 mg / kgBB. Celery extract was given for 14 days by gavage. Celery extract at doses of 100 and 200 mg / kgBB were able to improve the histological structure of the rats' kidneys induced by EG 0.75% and AK 2%. Keywords : celery, glomerular diameter, protein deposits